Synthetic Biology Brings New Opportunity for Antibiotics Discovery - Tong, Yaojun; Deng, Zixin; Bai, Linquan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
We are facing a complicated public health issue in the form of global drug shortages, including antibiotics. Synthetic biology empowers the next generation of antibiotics development, bringing us into a new era.